Driving dynamic colloidal assembly using eccentric self-propelled colloids - Ma, Zhan (2019)
Designing protocols to dynamically direct the self-assembly of colloidal particles has become an important direction in soft matter physics because of promising applications in the fabrication of dynamic responsive functional materials. Here, using computer simulations, we found that in the mixture of passive colloids and eccentric self-propelled active particles, when the eccentricity and self-propulsion of active particles are high enough, the eccentric active particles can push passive colloids to form a large dense dynamic cluster, and the system undergoes a novel dynamic demixing transition. Our simulations show that the dynamic demixing occurs when the eccentric active particles move much faster than the passive particles such that the dynamic trajectories of different active particles can overlap each other while passive particles are depleted from the dynamic trajectories of active particles. Our results suggest that this is in analogy to the entropy-driven demixing in colloid–polymer mixtures, in which polymer random coils can overlap with each other while depleting the colloids. More interestingly, we find that by fixing the passive colloid composition at a certain value with increasing density, the system undergoes an intriguing re-entrant mixing, and the demixing only occurs within a certain intermediate density range. This suggests a new way of designing active matter to drive the self-assembly of passive colloids and fabricate dynamic responsive materials.